Some advances in high-performance finite element methods. Issue 8 (7th October 2019) - Cen, Song; Wu, Cheng Jin; Li, Zhi; Shang, Yan; Li, Chenfeng
Abstract : Purpose: The purpose of this paper is to give a review on the newest developments of high-performance finite element methods (FEMs), and exhibit the recent contributions achieved by the authors' group, especially showing some breakthroughs against inherent difficulties existing in the traditional FEM for a long time. Design/methodology/approach: Three kinds of new FEMs are emphasized and introduced, including the hybrid stress-function element method, the hybrid displacement-function element method for Mindlin–Reissner plate and the improved unsymmetric FEM. The distinguished feature of these three methods is that they all apply the fundamental analytical solutions of elasticity expressed in different coordinates as their trial functions. Findings: The new FEMs show advantages from both analytical and numerical approaches. All the models exhibit outstanding capacity for resisting various severe mesh distortions, and even perform well when other models cannot work. Some difficulties in the history of FEM are also broken through, such as the limitations defined by MacNeal's theorem and the edge-effect problems of Mindlin–Reissner plate. Originality/value: These contributions possess high value for solving the difficulties in engineering computations, and promote the progress of FEM.